Техногенні небезпеки – загроза сталому розвитку міст - Рябініна, І. О. (ХНУРЕ, 2024)
Today, looking at the current state of cities, especially the consequences of the impact of hazard factors on the environment and humanity, causing damage to the economy and inhibiting the achievement of sustainable development goals, and, as a result, maintaining a high standard of living, there is an acute question of preventing the occurrence of various types of man-made hazards . The concept of sustainable development is aimed at finding a balance between economic development of the country, environmental protection, prevention of man-made disasters, sustainability of cities and social welfare of the population.
Keywords: техногенна небезпека